Architectural Katas : Spring 2022 (O'Reilly Media, Inc., 2022)
About Architectural Katas: What could be better than practicing software architecture with your handpicked dream team of architects? Participants in Architectural Katas, moderated by Neal Ford, work together in small groups of their choosing to solve a challenge an actual organization is facing. Everyone gets the chance to practice their craft with a real software architecture problem in a safe and social environment, and the finalists and winners earn well-deserved bragging rights (not to mention an intriguing line on their résumé). Plus a selected organization will have some of its gnarliest software architecture problems solved.